2010
DOI: 10.1007/s10620-010-1374-3
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Depletion Impairs Cell Proliferation in Adult Human Duodenum: Identification of Potential Effectors

Abstract: Riboflavin depletion in adult humans impairs proliferation and proliferative potential of intestinal cells, which may have implications for gastrointestinal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The wide spectrum of existence, function and localization of all these FAD dependent enzymes, raises the problem of their biogenesis route and dependence on FAD availability in each organelle. Given this multiplicity of cellular functions, it is not surprising that inadequate riboflavin availability, as well as derangements in FAD homeostasis, may be causative of cell degeneration and cancer (Powers 2003;Nakano et al 2011;P o w e r se ta l2011), as well as severe metabolic defects some of which are treatable with high doses of the vitamin (Gregersen 1985;G i a n a z z ae ta l2006;B a r i l e et al 2013).…”
Section: Communicated By: Manuel Schiffmentioning
confidence: 99%
“…The wide spectrum of existence, function and localization of all these FAD dependent enzymes, raises the problem of their biogenesis route and dependence on FAD availability in each organelle. Given this multiplicity of cellular functions, it is not surprising that inadequate riboflavin availability, as well as derangements in FAD homeostasis, may be causative of cell degeneration and cancer (Powers 2003;Nakano et al 2011;P o w e r se ta l2011), as well as severe metabolic defects some of which are treatable with high doses of the vitamin (Gregersen 1985;G i a n a z z ae ta l2006;B a r i l e et al 2013).…”
Section: Communicated By: Manuel Schiffmentioning
confidence: 99%
“…A role for RF in protein folding in the endoplasmic reticulum has also been identified [ 2 ]. More recent studies have identified anti-oxidant [ 3 – 5 ] and anti-inflammatory [ 6 ] properties for RF as well as a role in normal immune function [ 7 , 8 ], and in the maintenance of normal intestinal homeostasis [ 9 ]. Thus, disturbance in normal RF homeostasis is expected to lead to negative health consequences, which include degenerative changes in the nervous system, anemia, cataract and growth retardation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Nakano and co‐workers found that duodenal biopsies from riboflavin‐deficient human subjects had shallower crypt depths and less Ki67 + cells; they further showed that in intestinal Caco‐2 cells, depletion of riboflavin altered the expression of cell cycle genes, which lead to cell cycle arrest at G2‐mitosis transition. [ 157 ] In another study on HCT116, LS174T, and SW480 cell lines, folate was demonstrated to increase both cell proliferation and genomic DNA methylation level. [ 158 ] Additionally, vitamin K2 was reported to promote absorptive lineage differentiation, and reduce EGF‐induced proliferation in Caco‐2 cells.…”
Section: Gut Microbial Metabolites and Intestinal Stem Cell Activitiesmentioning
confidence: 99%